2007
DOI: 10.1007/s00330-007-0767-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of left ventricular function with dual-source CT in comparison to cardiac magnetic resonance imaging: initial findings

Abstract: Cardiac magnetic resonance imaging and echocardiography are currently regarded as standard modalities for the quantification of left ventricular volumes and ejection fraction. With the recent introduction of dual-source computedtomography (DSCT), the increased temporal resolution of 83 ms should also improve the assessment of cardiac function in CT. The aim of this study was to evaluate the accuracy of DSCT in the assessment of left ventricular functional parameters with cardiac magnetic resonance imaging (MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 19 publications
(17 reference statements)
2
39
1
Order By: Relevance
“…In addition, emergency patients and those with heart pacemakers or metallic foreign bodies cannot be routinely examined by MRI. Domestic and foreign scholars (Yamamuro et al, 2005;Busch et al, 2008) used the results of MRI measurement on cardiac function as a standard with which to comparemulti-slice spiral CT MSCT and echocardiography in the measurement of left ventricular function. They found that MSCT is more accurate and reliable than ultrasound measurements of left ventricular function, and that spatial resolution in CT images is superior to MRI, allowing the inner and outer membrane profile of heart, myocardium, and its accessory structure to be displayed more clearly, and facilitating tracing the inner and outer membrane profiles of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, emergency patients and those with heart pacemakers or metallic foreign bodies cannot be routinely examined by MRI. Domestic and foreign scholars (Yamamuro et al, 2005;Busch et al, 2008) used the results of MRI measurement on cardiac function as a standard with which to comparemulti-slice spiral CT MSCT and echocardiography in the measurement of left ventricular function. They found that MSCT is more accurate and reliable than ultrasound measurements of left ventricular function, and that spatial resolution in CT images is superior to MRI, allowing the inner and outer membrane profile of heart, myocardium, and its accessory structure to be displayed more clearly, and facilitating tracing the inner and outer membrane profiles of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using a moving heart-phantom by Mahnken et al [18] showed a good correlation between DSCT and MRI, with no significant differences, which is in accordance to the present in-vivo study. Only two small studies in patients are available at the present time [19,20]. A striking difference between the two studies is the wide B-A interval in the study by Busch et al [20] in which two different post-processing softwarepackages have been implemented for the MRI and DSCT on the one hand, and the narrow B-A interval in the study by Brodoefel et al [19] in which the same post-processing tool was used for both investigations on the other hand, suggesting a possible effect of the post-processing on the results.…”
Section: Discussionmentioning
confidence: 99%
“…18 The use of DSCT for the determination of ventricular volumes and EF in comparison to CMR showed similarly good results: EDV was underestimated by 3.7 ml, while ESV and EF were overestimated by 2.6 ml and 3.8%, respectively. 19 In another publication by Greupner et al, MDCT was compared with CMR, 2D echocardiography, and 3D echocardiography for the analysis of LV global function after coronary angiography. The study showed comparable limits of agreement for both MDCT and 2D echocardiography in the evaluation of EF vs. CMR.…”
Section: D and 3d Echocardiographymentioning
confidence: 99%